PSO-based path navigation system for visually impaired people - Tuan Shazana binti Tuan Yusof (Kulliyyah of Engineering,International Islamic University Malaysia, 2018)
Navigating or wayfinding is difficult to achieve for people with vision disability. They have to depend on their other senses such as hearing, smell and touch to perceive and be aware of the environment. With the advancement of technology, a variety of navigation devices have been developed to help visually impaired people (VIP) travelling independently. In Malaysia, VIP preferred to use white cane as a daily navigating tool despite various type of navigation devices in the market. This is due to its simplicity, foldable and affordable. However, VIP are having difficulties to navigate in an unfamiliar environment as the cane does not provide spatial information to the users. Therefore, this thesis presents Positioning Solution for Visually Impaired, PoSVI-Cane, an affordable smart cane with path planning module installed to the system. The goal of the path planning is to identify a route from an origination point to a destination point while avoiding static obstacles. In this thesis, the length and the smoothness of the path are the only constraints that will be considered for optimal path. Particle Swarm Optimization (PSO) is implemented to find optimal path based on predetermined waypoints. Waypoints can be described as a reference points or an intermediate point on a route. Constriction factor, X is incorporated into the velocity update equation of PSO to tackle premature convergence problem that frequently occurred in standard PSO formulation. The results show that Constriction factor PSO (CFPSO) able to give optimal path given selected destination from the system. Since it is crucial for the VIP to know their whereabouts, this device is equipped with Global Positioning System (GPS) to extract the position information of users. PoSVI-Cane comprises of a white cane and navigation control unit. The developed device able to complement white cane functionality by adding features such as providing verbal instruction to direct and help VIP reach their destination safely in an unfamiliar environment.